Diffusion Kurtosis Imaging and Intravoxel Incoherent Motion in Differentiating Nasal Malignancies. (20th November 2019) - Xiao, Zebin; Tang, Zuohua; Zheng, Chunquan; Luo, Jianfeng; Zhao, Keqing; Zhang, Zhongshuai
Abstract : Objectives/Hypothesis: To evaluate the usefulness of diffusion kurtosis imaging (DKI) and intravoxel incoherent motion (IVIM) in the differentiation of sinonasal malignant tumors (SNMTs) with different histological types. Study Design: Retrospective observational and diagnostic study. Methods: Sixty‐five patients with SNMTs who underwent DKI and IVIM were enrolled in this retrospective study, including 27 squamous cell carcinomas (SCCs), 13 olfactory neuroblastomas (ONBs), 14 malignant melanomas (MMs) and 11 lymphomas. The kurtosis (K) and diffusion coefficient (Dk) from DKI and the pure diffusion coefficient ( D ), pseudodiffusion coefficient ( D* ), perfusion fraction ( f ), and the product of D* and f ( f ∙ D* ) from IVIM were measured. Kruskal‐Wallis and Dunn multiple comparison tests with Bonferroni correction, receiver operating characteristic curve, and logistic regression analyses were used for statistical analysis. Results: Lymphomas demonstrated the highest K values but lowest Dk, D, D*, f, and f ∙ D* values among these four malignant tumors. ONBs exhibited high K values and MMs had highest D*, f, and f ∙ D* values. The cutoff value of ≤0.887 × 10 −3 mm 2 /sec for f ∙ D* provided a sensitivity, specificity, and an accuracy of 100%, 98.1%, and 98.5%, respectively, for differentiating lymphomas from the other three entities. The combination of f ∙ D* and D values showed a sensitivity of 92.9% and a specificity of 92.5% for the discrimination of MMs from ONBs and SCCs. The K value was useful for differentiating ONBs from SCCs, with a threshold value of 0.942 (sensitivity, 84.6%; specificity, 63.0%). Conclusions: The combined use of DKI and IVIM is helpful for differentiating among four histological types of SNMTs. Level of Evidence: 3 Laryngoscope, 2019